2016
DOI: 10.1186/s12957-016-1017-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of contrast-enhanced computed tomography and contrast-enhanced magnetic resonance imaging of small renal masses in real practice: sensitivity and specificity according to subjective radiologic interpretation

Abstract: BackgroundThe aim of this study was to investigate the diagnostic accuracy of contrast-enhanced computed tomography (CT) and contrast-enhanced magnetic resonance imaging (MRI) of small renal masses in real practice.MethodsContrast-enhanced CT and MRI were performed between February 2008 and February 2013 on 68 patients who had suspected small (≤4 cm) renal cell carcinoma (RCC) based on ultrasonographic measurements. CT and MRI radiographs were reviewed, and the findings of small renal masses were re-categorize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 32 publications
0
43
0
2
Order By: Relevance
“…CT scan sensitivity reaches more than 90% in the diagnosis of renal tumours smaller than 2 cm and almost 99.9% when the tumour is larger than 2 cm, but diagnosis of RCCs sensitivity ranges from 60% to 79% and specificity ranges from 44% to 99.9%. That is why radiological diagnosis of renal tumours must be confirmed by a histological examination (19,20). The main advantage of CT examination over MRI or UG is the absorption of X-rays, which are expressed in Hounsfield units (different types of kidney cancer -light cells, papillary cells, and chromophobe cells -have different densities) (21).…”
Section: Discussionmentioning
confidence: 99%
“…CT scan sensitivity reaches more than 90% in the diagnosis of renal tumours smaller than 2 cm and almost 99.9% when the tumour is larger than 2 cm, but diagnosis of RCCs sensitivity ranges from 60% to 79% and specificity ranges from 44% to 99.9%. That is why radiological diagnosis of renal tumours must be confirmed by a histological examination (19,20). The main advantage of CT examination over MRI or UG is the absorption of X-rays, which are expressed in Hounsfield units (different types of kidney cancer -light cells, papillary cells, and chromophobe cells -have different densities) (21).…”
Section: Discussionmentioning
confidence: 99%
“…26 They also stated that the diagnostic accuracy of CT and MRI was weak in subjective radiological interpretation in clinical practice. 27 Since needle biopsy on which there is conflicting information on its use for the diagnosis of RCC doesn't conform to oncological principles and the risk of the tumor seeding during biopsy, it is not recommended for the diagnosis of suspected renal lesions. 28 Other indicators which may predict the histopathology of renal masses other than the imaging methods were also covered in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in a study concerning the accuracy of CT for detecting renal tumors were based on a scoring system varying from "definitely not cancer" to "definitely solid cancer". That study reported an accuracy of 79% for detection of benign and malignant renal masses [35]. The detection of smaller tumors can especially pose a challenge [36,37].…”
Section: Tumor Detectionmentioning
confidence: 94%
“…The sensitivity and specificity for prediction of RCC in case of a renal tumor from CT findings has been described as 60% to 79% and 44% to 100%, respectively [35,42]. Although these findings may be influenced by tumor size, because a 1 cm increase in tumor size is associated with a 16% increase in the odd of malignancy [46].…”
Section: Accuracymentioning
confidence: 99%